IV Sodium Ferric Gluconate Complex in Patients Hospitalized Due to Acute Decompensated Heart Failure and Iron Deficiency. (6th January 2022) - Borreda, Itay; Zukermann, Robert; Epstein, Danny; Marcusohn, Erez
Background: Patients suffering from heart failure (HF) and iron deficiency (ID) have worse outcomes. Treatment with intra-venous (IV) ferric carboxymaltose has been shown to reduce HF rehospitalizations and to improve functional capacity and symptoms in patients with HF and reduced ejection fraction (HFrEF). However, IV ferric carboxymaltose is significantly more expensive than IV sodium ferric gluconate complex (SFGC) limiting its availability to most HF patients around the globe. Methods: A retrospective analysis comparing patients admitted to internal medicine or cardiology departments between January 2013 to December 2018 due to acute decompensated HF (ADHF) and treated with or without IV SFGC on top of standard medical therapy. Results: During the study period, a total of 1863 patients were hospitalized due to ADHF with either HFrEF or HF with preserved ejection fraction (HFpEF). Among them, 840 patients had laboratory evidence of iron deficiency (absolute or functional) and met the inclusion criteria. One hundred twenty-two of them (14.5%) were treated with IV SFGC during the index hospitalization. Patients treated with IV iron were more likely to have history of ischemic heart disease, atrial fibrillation, and chronic kidney disease. The rate of readmissions due to ADHF was similar between the groups at 30 days, 3 months, and 1 year. Conclusion: High risk patient hospitalized to ADHF and treated with IV SFGC showed comparable ADHF readmission rates, compared to those who did not receive iron supplementation.